INDICATEURS OF THE EXCELLENT PUBLIC RELATION PRACTICE - Ali, Khalaf Kareem Kyoosh (ALBAHITH ALALAMI, 2020)
« This paper presents the indicators of the development of excellent public relations in the institutions of higher education that are possible for three contextual variables: institutional, professional, professional, and effective communication. Therefore, the study used six indicators to measure the excellent public relations in institutions of higher education and scientific research. These indicators are based on the theory of excellence in public relations . Research Objectives: The aim of the research paper is to uncover the institutional, professional, and professional indicators of effective communication of excellent public relations in higher education institutions. Research hypothesis : There is a relationship between the indicators of public relations (institutional, professional and effective communication) and the practice of its excellent work in universities and colleges in Wasit . Research Methodology and Methodology: The methodology used in the research is descriptive. A descriptive sample of 30 respondents was selected. The target population in the research is (the contact person). Research results : The results of the research revealed that institutional indicators of excellent public relations in educational institutions are concerned with the management and strategic planning of the organization . The professional indicators for excellent public relations in the educational institutions provide excellent technical and administrative personnel. The effective communication indicators showed that they contribute to the application of the symmetrical model of communication and the Effectiveness in communication. Research Recommendations : The researcher recommends that the academic institutions of public relations contribute to the production of an excellent public relations behavioral work code as an indicator of the ideal in the work of the institution, and the need for a regulatory context for the management of public relations which is supported in institutions of higher education.